The Non-linear Relationship Between Normal Range Systolic Blood Pressure and Cardiovascular or All-Cause Mortality Among Elderly Population - Sun, Shuo; Liu, Xiao-cong; He, Guo-dong; Lo, Kenneth; Feng, Ying-qing; Huang, Yu-qing (Frontiers in Cardiovascular Medicine, 2021)
Purpose: The aim was to explore the association of normal range SBP with cardiovascular and all-cause mortality in older adults without hypertension. Methods: Participants aged ≥ 65 years without hypertension and those had an SBP level between 90 and 129 mmHg were included from the National Health and Nutrition Examination Survey (1999–2014). SBP was categorized into: 90–99, 100–109, 110–119, and 120–129 mmHg. Multivariate Cox regression was performed with hazard ratio (HR) and 95% confidence interval (CI). Results: Of the 1,074 participants, 584 were men (54.38%). Compared with participants with SBP level ranged 110 to 119 mmHg, the HRs for all-cause mortality risk was 1.83 (95% CI: 1.04, 3.23) for SBP level ranged 90 to 99 mm Hg, 0.87 (95% CI: 0.54, 1.41) for SBP level ranged 100 to 109 mmHg, and 1.30 (95% CI: 0.96, 1.75) for SBP level ranged 120 to 129 mmHg (P for trend = 0.448), and the HR for cardiovascular mortality risk was 3.30 (95% CI: 0.87, 12.54) for SBP level ranged 90 to 99 mmHg, 0.35(95% CI: 0.08, 1.56) for SBP level ranged 100 to 109 mmHg, and 1.75 (95% CI: 0.78, 3.94) for SBP level ranged 120 to 129 mm Hg (P for trend = 0.349) after confounders were adjusted. Conclusion: These were a nonlinear association of normal range SBP level with all-cause and cardiovascular death in older adults.